Two types of functionally distinct Ca2+ stores in hippocampal neurons - Hsing-Jung Chen-Engerer (Nature Portfolio, 2019)
It is generally assumed, from previous studies in cerebellar Purkinje neurons, that IP3 and Ry receptors share the same intracellular Ca2+ pool. In this study, the authors demonstrate the existence of two functionally distinct Ca2+ stores in mouse CA1 pyramidal neurons by showing that refilling of IP3-sensitive stores relies on Orai2 channels, whereas Ry-sensitive stores involve VGCCs for spontaneous store refilling